Textile-based batteries with nanofiber interlayer - Resuli, R.; Turhan, I.; Ehrmann, Andrea; Blachowicz, T. (AIMS Energy)
Textile batteries are of utmost interest for the emerging field of electronic textiles. Several research groups work on this topic, developing either fiber-based batteries or planar alternatives, e.g. by coating textile fabrics with metallic electrodes and an electrolyte between them. Since usual non-toxic electrolytes are fluid, using them in a textile battery necessitates gelling them or embedding them in a sponge-like matrix to avoid diffusion through the textile electrodes. Here we report on measurements of textile batteries, prepared from different conductive woven fabrics with a nanofiber mat as an interlayer filled with iodine-triiodide solution. Firstly, the highest voltages were achieved combining metal electrodes with a carbon electrode, showing that the electrolyte in this system is part of the redox system. Second, the metal electrodes were destroyed after short times, suggesting that iodine-triiodide is not an ideal choice for an electrolyte, although this material is often used. Finally, we show that even without setting up the complete battery, the electrolyte slowly destroys the metal layers, while it is itself degraded by photo-oxidation, underlining the necessity to find non-toxic, environmentally-friendly alternatives for iodine-triiodide to enable long-term storage. Assuming non-solid state for electrolytes, the level of their confinement by different types of corrugated materials was tested.